A study on the prevalence of refractive errors among school children of 10-16 years in Surendranagar district, Gujarat - Parmar, Ankita; Kartha, Girija; Baria, Manish (International Journal Of Community Medicine And Public Health, 2017)
Background: Refractive error could be considered as an avoidable condition among various conditions leading to visual disabilities in children. Present study was conducted with the objective of estimating the prevalence of refractive errors among school children in Surendranagar district. Methods: The study was conducted among the school going children of 10-16 years age group of Surendranagar district of Gujarat state. Total 600 students were examined from rural and urban schools of the district. The study was carried out through oral questionnaire method using pre-designed and pretested Performa followed by ocular examination. Results: Overall prevalence of refractive errors was found to be 29.5%. Headache was the single most common symptom reported by 38.58% children. Nearly 36.54% boys and 36.98% girls had moderate visual impairment while 4.80% boys and 2.75% girls had severe visual impairment. Among the children having refractive errors 61.02% children did not use spectacles. Conclusions: The study shows that children among 10-16 years are at risk of developing refractive errors and many of them are not aware of the refractive errors.